2018
DOI: 10.1186/s12905-018-0526-z
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner sexual violence and risk for femicide, suicidality and substance use among women in antenatal care and general out-patients in Thailand

Abstract: BackgroundLittle is known about the occurrence and health consequences of intimate partner sexual assault. The aim of this study was to assess the prevalence and correlates of sexual assault in the context of intimate partner violence (IPV) in Thailand.MethodsIn a cross-sectional survey adult female participants were systematically screened (self-administered or interview administered) for IPV in antenatal care and general outpatient clinics in nine randomly selected hospitals in two provinces in the central r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 25 publications
(44 reference statements)
2
17
0
1
Order By: Relevance
“…In line with previous research findings (Issahaku, 2015;Hahm et al, 2017;Honda et al, 2018;Pengpid et al, 2018), these women who had experienced abusive relationships reported physical pain, a low level of self-esteem and self-worth, depression and trauma-related symptoms. A sense of disempowerment occurred in particular when they felt that there was nobody to help them and they had nowhere to go.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In line with previous research findings (Issahaku, 2015;Hahm et al, 2017;Honda et al, 2018;Pengpid et al, 2018), these women who had experienced abusive relationships reported physical pain, a low level of self-esteem and self-worth, depression and trauma-related symptoms. A sense of disempowerment occurred in particular when they felt that there was nobody to help them and they had nowhere to go.…”
Section: Discussionsupporting
confidence: 90%
“…Participants in this research were exposed to several kinds of sexual violence including forced intercourse, unusual and/or uncomfortable sexual activities and requests, and being made to have feelings of risk and danger in their marital relationship. In line with national and global research findings (Fallah et al, 2015;Pengpid et al, 2018), participants disclosed a mixture of physical and emotional abuse while they were experiencing IPSV, leading to physical problems including pain and even abortion, and emotional problems such as feelings of disempowerment, dehumanization, being degraded, depression, and a sense of being worthless.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Drinking serves as a symbol of masculine gender identity, and alcohol is used as a tool to justify men's IPV and violence against other family members [19]. Studies on domestic violence in Thailand in the literatures are all in the context of IPV in married or cohabitating heterosexual relationships [4,[20][21][22]. The prevalence of lifetime experience of IPV in Thailand varied from 16% in a survey of 1444 women in 4 provinces in 4 regions [20] to 27% in a survey of 580 women in seven Bangkok slums [4].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of lifetime experience of IPV in Thailand varied from 16% in a survey of 1444 women in 4 provinces in 4 regions [20] to 27% in a survey of 580 women in seven Bangkok slums [4]. The prevalence of IPV in the past 12 months was 1.5% among women in a hospital-based crosssectional study [21]. The definitions of IPV in these mentioned studies included acts of psychological, physical and sexual violence.…”
Section: Introductionmentioning
confidence: 99%